THE INFLUENCE OF SEGMENTING, TARGETING AND POSITIONING STRATEGIES ON PURCHASE DECISIONS AT ZHALSA.ID STORES IN LHOKSUKON CITY - T Edyansyah; Juni Ahyar; Rico Nur Ilham; Chalirafi Chalirafi; Ikramuddin Ikramuddin (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
This study aims to see the effect of segmenting, targeting and positioning strategies on purchasing decisions at Zhalsa.Id Stores in Lhoksukon City. The sampling technique in this study is the accidental sampling technique. The sample taken in this study amounted to 130 consumers who bought at Zhalsa.Id Stores in Lhoksukon City. The results of this study indicate that partially segmenting and positioning variables have a positive and significant effect on purchasing decisions. While the targeting variable has no effect on purchasing decisions at the Zhalsa.Id Store in Lhoksukon City. Segment, targeting and positioning variables simultaneously have a positive and significant effect on purchasing decisions at Zhalsa.Id Stores in Lhoksukon City.